Prepare a plan for the Total Productive Maintenance in the light of the concurrent engineering A Field Study in AL-Askandria General Company Machanical Industries and AL-Musaib Electric Power Station - عبد الرضا نغم يوسف; كاظم امير جواد (Journal of Economics and Administrative Sciences, 2018)
Strives Total Productive Maintenance to increase the overall effectiveness of the equipment through the early involvement in the design and manufacture of equipment productivity. It also operates in an environment of simultaneous engineering work on the synchronization of activities to take advantage of early information by maintenance engineers, design, operation, and that helps to reduce the faults and facilitate future maintenance tasks. Has adopted a search in the theoretical concept of the total maintenance productivity and concurrent engineering activities carried out during which the conjunction and the efforts of multi-functional work teams . After examining the faults in the company ( consumed ) suggest the researcher to design a new cover electric generator contributes to speed up access to the internal parts and filter the type of holidays and repaired . The proposed design can be manufactured at company plants ( manufacturer)، which adopts a cover according to the manufacture of parts prior cooperation mechanisms between the two companies . Research has achieved positive results is to reduce the time and costs by 14% . And facilitate disassembly and installation when implementing the reforms of the electric generator ( under discussion)